Influence of right and left bundle branch block in patients with cardiogenic shock and cardiac arrest: clinical investigation - Rusnak, Jonas; Schupp, Tobias; Weidner, Kathrin; Ruka, Marinela; Egner-Walter, Sascha; Forner, Jan; Schmitt, Alexander; Akin, Muharrem; Tajti, Péter; Mashayekhi, Kambis; Ayoub, Mohamed; Akın, Ibrahim; et al. (Critical care medicine, 2025)
OBJECTIVES: - The study investigates the prognostic impact of right bundle branch block (RBBB) and left bundle branch block (LBBB) in patients with cardiogenic shock (CS) compared with no bundle branch block (BBB). In patients with heart failure, existence of RBBB and LBBB has influence on prognosis. - DESIGN: - Prospective registry-study. - SETTING: - ICU of a tertiary academic hospital in Germany. - PATIENTS: - Adult patients with CS. - INTERVENTIONS: - None. - MEASUREMENTS AND MAIN RESULTS: - Consecutive patients with CS were included. The prognostic impact of RBBB and LBBB on 30-day all-cause mortality was tested within the entire cohort and in the subgroup of CS patients with cardiac arrest at admission. The final study cohort comprised 248 patients. Patients with RBBB showed the highest 30-day all-cause mortality followed by LBBB and no BBB (72.5% vs. 52.9% vs. 50.0%; log-rank p = 0.015). These findings were consistent even after solely including CS patients with cardiac arrest (90.0% vs. 73.3% vs. 62.2%; log-rank p = 0.008). After adjustment for lactate, norepinephrine, troponin I, Acute Physiology Score, Society of Cardiovascular Angiography & Interventions shock stage, and heart rate in a multivariable Cox regression analysis, RBBB still revealed a negative impact on 30-day all-cause mortality (hazard ratio [HR], 1.807; 95% CI, 1.107-2.947; p = 0.018), whereas LBBB was not associated with 30-day all-cause mortality. In this multivariable Cox regression model lactate (HR, 1.065; 95% CI, 1.018-1.115; p = 0.006), troponin I (HR, 1.003; 95% CI, 1.001-1.005; p = 0.001), and Acute Physiology Score (HR, 1.033; 95% CI, 1.001-1.066; p = 0.041) were as well associated with 30-day all-cause mortality. Finally, no association of RBBB was found with the incidence of liver or severe renal failure. - CONCLUSIONS: - Besides the Acute Physiology Score, lactate, and troponin levels, RBBB was associated with an increased 30-day all-cause mortality in consecutive CS patients with and without cardiac arrest, whereas LBBB showed no prognostic impact.